Green and environment-friendly sea sand mortar as well as preparation method and application thereof
By using bran carbonate and sodium silicate as composite alkali exciters, combined with sea sand and other gelling materials, a low-carbon, green and environmentally friendly sea sand mortar was prepared, which solved the problem of difficult operation of composite alkali exciters and shortage of natural river sand resources, and achieved high strength, short condensation time and low carbon emission effects.
Patent Information
- Application Number
- CN202411948894.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art has problems such as difficult and high risk in the use of composite alkali triggers. At the same time, natural river sand resources are short of, and sea sand may affect the long-term performance of concrete when it is not treated.
Potassium carbonate and sodium silicate are used as composite alkali exciters, combined with sea sand, slag powder and fly ash, and a low-carbon, green and environmentally friendly sea sand mortar is prepared by synergistically using gelled materials and fine aggregates.
It significantly improves the compressive strength and flexural strength of sea sand mortar, shortens the condensation time, reduces the use of sodium hydroxide, reduces the emission of carbon dioxide, and alleviates the tightness of natural river sand resources.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a green and environmentally friendly sea sand mortar and a preparation method and application thereof. Background Art
[0002] With the acceleration of global urbanization and the continuous expansion of infrastructure construction, the demand for concrete has increased dramatically. As one of the main components of concrete, the production of cement has also continued to rise. However, for every ton of cement clinker produced during cement production, about 0.8 tons of carbon dioxide will be emitted, which has caused serious greenhouse gas emissions and climate change impacts on the environment. In order to reduce the pressure of cement production on the environment, researchers have begun to seek new low-carbon building materials to replace ordinary Portland cement, especially in the field of concrete preparation. Promoting green, environmentally friendly, low-carbon, and high-performance alternative materials has become an important research direction.
[0003] In recent years, the technology of using alkali-activated cementitious materials has gradually attracted attention. Alkali-activated materials usually refer to the use of alkaline solutions to activate certain industrial wastes (such as slag, fly ash, etc.) to generate gel-like substances (such as NASH gel), thereby improving their mechanical properties and durability. This type of material has excellent properties such as rapid hardening, high temperature resistance, and acid corrosion resistance, and is widely used in low-carbon concrete and other building materials. There are still some problems in the use of composite alkali activators in the prior art. In most studies, the composite alkali activator mainly uses a mixed solution of sodium silicate and sodium hydroxide. Although this activator performs well in the activation effect, sodium hydroxide has strong alkalinity and strong corrosiveness, and there are problems of difficulty in operation and high danger during use and preparation. In addition, an important component of mortar is natural river sand, which is a non-renewable resource. With the rapid development of the construction industry, the consumption of river sand has increased year by year, and the output of river sand has become less and less. Natural river sand is facing an increasingly scarce situation, while sea sand, as a rich natural resource, is increasingly used in building materials. However, due to the changes in particle size distribution, salt content and other impurities of sea sand, the use of untreated sea sand as aggregate may affect the long-term performance of concrete. Therefore, the use of sea sand in mortar or concrete often needs to be combined with other optimization measures to ensure the stability and durability of the final product.
[0004] Therefore, it is necessary to develop a green and environmentally friendly sea sand mortar to solve the above problems. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a sea sand mortar, which has good mechanical properties, short setting time, and is low-carbon and green and environmentally friendly.
[0006] The second aspect of the present invention also provides a method for preparing sea sand mortar.
[0007] The third aspect of the present invention also provides an application of sea sand mortar.
[0008] According to the first aspect of the present invention, the sea sand mortar provided by the embodiment comprises sea sand, a composite alkali activator, a cementitious material and water;
[0009] The composite alkali activator includes potassium carbonate and sodium silicate; the cementitious material includes slag powder and fly ash.
[0010] The sea sand mortar according to the embodiment of the present invention has at least the following beneficial effects:
[0011] The present invention ensures that the mortar has high strength and short setting time through the coordinated use of cementitious materials, fine aggregates and composite alkali activators, and has the characteristics of low carbon and green environmental protection. The present invention uses potassium carbonate and sodium silicate as composite alkali activators and sea sand as fine aggregate. Compared with the alkali activators and river sand used in traditional technologies, the present invention significantly improves the compressive strength and flexural strength of sea sand mortar; the sea sand mortar produced by the present invention has a shorter setting time, which makes the mortar suitable for rapid repair and construction applications, especially in scenes where rapid hardening is urgently needed, such as wall repair and concrete structure filling; the present invention uses low-corrosion, low-alkali composite alkali activators and sea sand, which reduces the use of sodium hydroxide, reduces the safety risks in the production process, and reduces carbon dioxide emissions by replacing traditional cement.
[0012] The present invention adopts potassium carbonate and sodium silicate as composite alkali activators. Potassium carbonate, as a weak base, can effectively replace sodium hydroxide, reduce the corrosiveness and operation difficulty of the alkali activator, and solve the problem of poor operation safety of the existing composite alkali activator.
[0013] The present invention uses sea sand to replace traditional river sand as aggregate, which reduces the construction industry's dependence on natural river sand and alleviates the shortage of natural sand resources. At the same time, sea sand can be widely used without reducing the performance of mortar after simple pretreatment, and has the characteristics of high resource utilization efficiency.
[0014] According to some embodiments of the present invention, the content of the composite alkali activator is 14.2 wt % to 16.2 wt % of the gelling material.
[0015] According to some embodiments of the present invention, the content of potassium carbonate is 5.9 wt% to 9.5 wt% of the gelling material, for example, 5.9 wt%, 6.7 wt%, 8.3 wt%, or 9.5 wt%.
[0016] According to some embodiments of the present invention, the sodium silicate content of the gelling material is 5.9 wt % to 9.5 wt %, for example, 5.9 wt %, 6.7 wt %, 8.3 wt %, or 9.5 wt %.
[0017] According to some embodiments of the present invention, the content of the composite alkali activator accounts for 14.2 wt % to 16.2 wt % of the gelling material.
[0018] According to some embodiments of the present invention, the particle size of the sea sand is 0.15-4.75 mm.
[0019] According to some embodiments of the present invention, the dry apparent density of the sea sand is 2400-2600 kg / m 3 .
[0020] Preferably, the dry apparent density of the sea sand is 2500-2600 kg / m 3 .
[0021] More preferably, the dry apparent density of the sea sand is 2534 kg / m 3 .
[0022] According to some embodiments of the present invention, the fineness modulus of the sea sand is 2.2-2.7.
[0023] Preferably, the fineness modulus of the sea sand is 2.3 to 2.6.
[0024] More preferably, the fineness modulus of the sea sand is 2.56.
[0025] According to some embodiments of the present invention, the mass ratio of the slag powder to fly ash is 1:1 to 3:1.
[0026] Preferably, the mass ratio of the slag powder to fly ash is 3:1.
[0027] According to some embodiments of the present invention, the slag powder is selected from S95 granulated blast furnace slag powder (GGBS).
[0028] According to some embodiments of the present invention, the fly ash is selected from Class I fly ash (FS).
[0029] According to some embodiments of the present invention, the water-cement ratio of the sea sand mortar is 0.35-0.45, for example, it can be 0.35, 0.4, or 0.45.
[0030] According to some embodiments of the present invention, the mass ratio of the cementitious material to the sea sand is 1:1 to 1:1.5, for example, it can be 1:1, 1:1.2, 1:1.3, 1:1.4, or 1:1.5.
[0031] If the water-cement ratio of the sea sand mortar described in the present invention is too low, the mold cannot be installed due to the too fast setting time, and if it is too high, the strength cannot be guaranteed. The mortar with limited cementitious materials and sea sand quality ratio can be denser.
[0032] According to the second aspect of the present invention, the method for preparing the sea sand mortar provided in the embodiment comprises the following steps:
[0033] S1, pre-treating sea sand;
[0034] S2, mixing slag powder, fly ash and sea sand in proportion;
[0035] S3. Add a composite alkali activator and stir to obtain sea sand mortar.
[0036] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:
[0037] The preparation method of the present invention is simple to operate and does not require advance preparation, and the compressive and flexural strengths of the prepared mortar are improved. The present invention first puts the cementitious material and sea sand to fully blend and stir, and finally puts the composite alkali activator to better carry out the hydration reaction. The purpose of using two stirring treatments is to ensure that the material will not be scattered due to too fast a rotation speed at a low speed, and the high speed is because the alkali-activated hydration process is rapid, so as to facilitate the mixing of the alkali activator and the cementitious material.
[0038] According to some embodiments of the present invention, in step S1, the pretreatment includes washing and drying.
[0039] According to some embodiments of the present invention, in step S1, the chloride ion content in the pretreated sea sand is less than 0.02%.
[0040] According to some embodiments of the present invention, in step S2, the stirring treatment rate is: rotation 135r / min~145r / min, revolution 57r / min~67r / min.
[0041] Preferably, in step S2, the stirring treatment rate is: rotation 125r / min, revolution 62r / min.
[0042] According to some embodiments of the present invention, in step S2, the stirring treatment time is 1 to 2 minutes.
[0043] According to some embodiments of the present invention, in step S3, the rate of the first stirring treatment is: rotation 135r / min to 145r / min, revolution 57r / min to 67r / min.
[0044] Preferably, in step S3, the stirring treatment rate is: rotation 125r / min, revolution 62r / min.
[0045] According to some embodiments of the present invention, the first stirring treatment lasts for 1 to 2 minutes.
[0046] According to some embodiments of the present invention, in step S3, the rate of the second stirring treatment is: rotation 275r / min~295r / min, revolution 115r / min~135r / min.
[0047] Preferably, in step S3, the speed of the second stirring treatment is: rotation 285 r / min, revolution 125 r / min.
[0048] According to some embodiments of the present invention, in step S3, the second stirring treatment lasts for 30 to 45 seconds.
[0049] A third aspect of the present invention provides an application of the above-mentioned sea sand mortar in a sea sand concrete structure.
[0050] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. DETAILED DESCRIPTION
[0051] The embodiments of the present invention are described in detail below, and the same or similar reference numerals throughout the embodiments represent the same or similar elements or elements with the same or similar functions. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0052] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0053] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.
[0054] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0055] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.
[0056] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0057] The slag powder is selected from S95 granulated blast furnace slag powder (GGBS), and the test report is shown in Table 1;
[0058] Table 1 Slag powder test report
[0059]
[0060] The fly ash is selected from Class I fly ash (FS), and the test report is shown in Table 2;
[0061] Table 2 Fly ash test report
[0062]
[0063] The dry apparent density of sea sand is 2534kg / m 3 , the fineness modulus is 2.56, and the particle grading screening is shown in Table 3;
[0064] Table 3 Particle grading screening results of sea sand
[0065]
[0066] Potassium carbonate (CAS No. 584-08-7) and sodium silicate (CAS No. 1344-09-8) were analytically pure and were obtained from Tianjin Xiangruixin Chemical Technology Co., Ltd.
[0067] Embodiments 1 to 4
[0068] Examples 1 to 4 provide a series of sea sand mortars, the component contents of which are shown in Table 4, and the preparation methods thereof are as follows:
[0069] 1) Weigh the analytically pure masses of slag powder, fly ash, sea sand, water, potassium carbonate and sodium silicate according to the mix ratio; mix water, potassium carbonate and sodium silicate together and stir them thoroughly to prepare a composite alkali activator; wherein the water-binder ratio is 0.4.
[0070] 2) Clean and moisten the mortar mixer in advance, wash the inner wall of the mixer with tap water, and wipe off excess water to ensure that there is no visible water on the inner wall of the mixer;
[0071] 3) Pour the ore powder, fly ash, silica ash, phosphorus slag powder, and the sea sand washed with clean water and dried into the mixture and stir at a stirring rate of: rotation 125 r / min, revolution 62 r / min, and time for 1.5 min;
[0072] 4) Add the composite alkali activator for the first stirring, the stirring rate is: rotation 125r / min, revolution 62r / min, time is 1min; then carry out the second stirring rate: rotation 285r / min, revolution 125r / min, time is 30s.
[0073] Table 4 Component contents of Examples 1 to 4 (unit: kg / m 3 )
[0074]
[0075]
[0076] Comparative Examples 1-2
[0077] Comparative Examples 1 to 1 provide a series of common alkali-activated mortars, the component contents of which are shown in Table 5, and the preparation methods thereof are the same as those of the embodiments of the present invention.
[0078] Table 5 Component contents of comparative examples 1 to 2 (unit: kg / m 3 )
[0079]
[0080] Performance Testing
[0081] After mixing the mortar according to the above ratios, test the mortar properties.
[0082] The experiment tested the 7d and 28d compressive strength and flexural strength, and the setting time of the mortar. The experimental results are shown in Tables 6 and 7.
[0083] Compression and flexural strength: "Test method for strength of cement mortar (ISO method)" GB / T 17671-2021;
[0084] Setting time: "Standard for test methods of basic properties of building mortar" JGJ / T70-2009;
[0085] The test method is to use a flexural and compressive strength tester and a Vicat instrument;
[0086] Table 6 Mechanical properties of Examples 1 to 4 and Comparative Examples 1 to 2
[0087]
[0088] Table 7 Coagulation time of Examples 1 to 4 and Comparative Examples 1 to 2
[0089]
[0090]
[0091] It can be seen from Tables 6 and 7 that the present invention uses sodium silicate and potassium carbonate as a composite alkali activator, uses sea sand as fine aggregate, and cooperates with cementitious materials to make the sea sand mortar have better mechanical properties, shorten the setting time, and reduce carbon dioxide emissions without the use of sodium hydroxide.
[0092] The 28d compressive strength of the formula of Example 4 of the present invention is as high as 52.9MPa, which is significantly better than Comparative Example 1 (34.1MPa), Comparative Example 2 (47.8MPa) and Comparative Example 3 (43.8MPa), indicating that the synergistic use of the composite alkali activator and sea sand in the present invention significantly improves the strength performance of the material, and the compressive strength reaches a relatively high strength in the application of this field, which is suitable for projects with high strength requirements. The flexural strength in the examples also remains at a high level, such as Example 1 (5.3MPa) and Example 4 (5.4MPa) are both higher than Comparative Example 3 (4.3MPa), and the flexural strength in the comparative example is significantly lower than that in the examples, indicating that the composite alkali activator and sea sand formula of the present invention have an improving effect on the overall mechanical properties of the mortar. In Examples 1 to 4, as the proportion of potassium carbonate in the composite alkali activator increases, the overall mechanical properties of the mortar become better, and as the proportion of sodium silicate increases, the mechanical properties of the mortar are also improved. However, if the sodium silicate content is too high, alkali efflorescence will occur during the curing process, resulting in a decrease in the mechanical properties and durability of the mortar. If the content of sodium silicate is too low, the cementitious material will not react completely, resulting in defects inside the mortar. The addition of potassium carbonate will improve fluidity, but the amount cannot exceed the range specified in the present invention.
[0093] The setting time in the examples is significantly lower than that in the comparative examples, and Example 4 (18 min) is the fastest, significantly better than the samples in all comparative examples, especially the 40 min setting time of comparative examples 1 and 2. This shows that the use of the composite alkali activator and sea sand of the present invention can effectively accelerate the setting process of the mortar, making it more efficient in practical applications, especially having a greater advantage in rapid repair applications.
[0094] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A sea sand mortar, characterized in that: The sea sand mortar comprises sea sand, a composite alkali activator, a cementitious material and water; The composite alkali activator includes potassium carbonate and sodium silicate; the cementitious material includes slag powder and fly ash.
2. The sea sand mortar according to claim 1, characterized in that: The content of the composite alkali activator is 14.2wt% to 16.2wt% of the cementitious material; preferably, the content of potassium carbonate is 5.9wt% to 9.5wt% of the cementitious material; preferably, the content of sodium silicate is 5.9wt% to 9.5wt% of the cementitious material.
3. The sea sand mortar according to claim 1, characterized in that: The mass ratio of the sodium silicate to the potassium carbonate is 1:0.7-1.
5.
4. The sea sand mortar according to claim 1, characterized in that: The particle size of the sea sand is 0.15-4.75 mm; preferably, the dry apparent density of the sea sand is 2400-2600 kg / m 3 ; Preferably, the fineness modulus of the sea sand is 2.2 to 2.
7.
5. The sea sand mortar according to claim 1, characterized in that: The mass ratio of the slag powder to the fly ash is 1:1 to 3:
1.
6. The sea sand mortar according to claim 1, characterized in that: The water-to-cement ratio of the sea sand mortar is 0.35-0.45; preferably, the mass ratio of the cementitious material to the sea sand is 1:1-1:1.
5.
7. A method for preparing sea sand mortar according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: S1, pre-treating sea sand; S2, mixing slag powder, fly ash and sea sand, and stirring; S3. Add a composite alkali activator and stir twice to obtain sea sand mortar.
8. The preparation method according to claim 7, characterized in that: In step S1, the pretreatment includes washing and drying; preferably, in step S1, the chloride ion content in the pretreated sea sand is less than 0.02%; preferably, in step S2, the stirring treatment rate is: rotation 135r / min~145r / min, revolution 57r / min~67r / min; preferably, in step S2, the stirring treatment time is 1~2min.
9. The preparation method according to claim 7, characterized in that: In step S3, the rate of the first stirring treatment is: rotation 135r / min~145r / min, revolution 57r / min~67r / min; preferably, in step S3, the time of the first stirring treatment is 30s~45s; preferably, in step S3, the rate of the second stirring treatment is: rotation 275r / min~295r / min, revolution 115r / min~135r / min; preferably, in step S3, the time of the second stirring treatment is 1~2min.
10. Use of the sea sand mortar according to any one of claims 1 to 6 in a sea sand concrete structure.
Citation Information
Cited By
Alkali-activated mortar based on low-carbon composite excitation system and preparation method of alkali-activated mortar
CN120717743A
Alkali-activated mortar based on low-carbon composite activation system and preparation method thereof
CN120717743B